2008
DOI: 10.1177/0275074008320711
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Nonprofit Coproduction of Public Service Delivery

Abstract: Americans have long formed nonprofits to voluntarily coproduce public services. However, demand perspectives on the development of the nonprofit sector and supply perspectives on the activation of civic engagement suggest potentially contradictory explanations of collective coproduction. Using the case of nonprofit support for public k-12 education, the authors explore the community- and school-level determinants of nonprofit coproduction of public education. Their findings suggest that nonprofit coproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 44 publications
3
70
0
1
Order By: Relevance
“…In particular, community human resources provide the skills, financial capacity, and awareness of community needs necessary for community engagement (Bekkers and Wiepking ). Also, resources available in the community drive the prevalence of nonprofit organizations and the size and health of the sector (Grønbjerg and Paarlberg ; Lecy and Van Slyke ; Paarlberg and Gen ; Saxton and Benson ).…”
Section: Community Philanthropy and Economic Structurementioning
confidence: 99%
“…In particular, community human resources provide the skills, financial capacity, and awareness of community needs necessary for community engagement (Bekkers and Wiepking ). Also, resources available in the community drive the prevalence of nonprofit organizations and the size and health of the sector (Grønbjerg and Paarlberg ; Lecy and Van Slyke ; Paarlberg and Gen ; Saxton and Benson ).…”
Section: Community Philanthropy and Economic Structurementioning
confidence: 99%
“…Modelling coproductive nonprofit organizational activity requires an understanding of complex community dynamics, since it is driven by both governmental and community needs as well as community resources (see for example Paarlberg and Gen, 2009). …”
Section: Applying the Ses Framework To Civil Society Questionsmentioning
confidence: 99%
“…The SES framework is helpful here in its ability to account for both internal capacity as well as external environmental variables such as socio-demographic differences that explain nonprofit formation and growth. For example, scholars have ascribed differences in nonprofit activity to rural/urban differences (Komp et al 2012), educational attainment (Grønbjerg & Paarlberg, 2001), income (Isham et al, 2006), and amount of social capital (Isham et al, 2006;Paarlberg & Gen, 2009). …”
Section: Applying the Ses Framework To Civil Society Questionsmentioning
confidence: 99%
“…Unmet demands in the quality and volume of educational services for their children inspires parents to invest additionally even in a relatively strong economic environment, let alone in a down economy [Nelson, Gazley 2014]. One research into the cooperation between American schools and their nonprofit partners has shown that the intensity of such interaction is influenced by both unsatisfied preferences about educational services, on the one hand, and financial and other resources required to establish nonprofit organizations, on the other hand [Paarlberg, Gen 2009].…”
Section: Doimentioning
confidence: 99%